INTEGRATED APPROACH IN TEACHING-LEARNING ENGLISH - Idaryani Idaryani (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
In Indonesia people speak vernacular languages as their mother tongues and Bahasa Indonesia as lingua franca however English as foreign language is considered as important language to learn. Therefore, even English is not significant means of communication in Indonesia, national curriculum has positioned English as one of prerequisite subjects in education. Since the learner of additional languages are expected to develop both of linguistic and communicative skill, teaching-learning process requires not only learner motivation but also appropriate and integrative pedagogical approach so that the students will learn English more easier. PPP method is suitable for the students to learn more about grammar which focuses on words, phrases and sentences.  Communicative language teaching (CLT) and task-based language teaching are appropriate to enhance speaking skills of learners which encourage them to be more engaged and be active in classroom activities and put the students as the centre of classroom activities. Thus the students will have more opportunity to apply the grammatical rules by practicing them through their speaking and writing. Content-based approach can help the students to discuss particular issue that common happen and associated with their discipline or life context. Classroom activity is very important to enable students to keep speaking and practice their English as much as possible so that the students can apply the use of grammatical functions in their activities in order to improve their productive skill.